EFFECT OF FRICTION STIR PROCESSING ON FATIGUE BEHAVIOR OF THIN DUAL PHASE (DP600) STEEL SHEETS - Saray, Onur; Yilmaz, Mumin; Ozturk Yilmaz, Imren (Tanger Ltd, 2018)
In this study, effects of Friction Stir Processing (FSP) on the deformation behavior of Dual Phase (DP600) steel sheets under static and cyclic loading were investigated. Fatigue tests were performed at a frequency of 15 Hz during repeated tension at a cycle asymmetry R = 0 and 10(6) loading cycles. DP600 steel reflected yield strength (sigma(y)) of 301 MPa and ultimate tensile strength (sigma(UTS)) of 621 MPa with uniform elongation of 21.3% and fractured after a total elongation of 34.7% in its as-received condition. After FSP, it was observed that the yield strength increased to 811 MPa and the ultimate tensile strength reached to 1054 MPa. This effective strength enhancement brought an acceptable decrease in ductility of the DP600 steel resulting in uniform elongation and elongation to failure of 6.3% and 13.0%, respectively. Based on obtained ductility values, it can be considered that, FSPed DP600 shows a deformation behavior that mostly dominated by the strain hardening. Static strength enhancement obtained by FSP of DP600 steel also yielded a favorable effect on the fatigue behavior and stress level leading to transition to the infinite life. As a result of the fatigue tests, it was determined that the fatigue limit of the as-received DP600 steel increased from 350 MPa to 480 MPa after the applied FSP. Experimental results obtained in the study mainly indicate that, FSP is an easy to apply and practical procedure which provides significant enhancement on the mechanical performance of DP600 steel under both static and cyclic loading conditions.
27th International Conference on Metallurgy and Materials (METAL) -- MAY 23-25, 2018 -- Brno, CZECH REPUBLIC
Keywords: Friction stir processing; DP steel; fatigue behavior; sheet metal